Studi Kandungan Boraks pada Bakso dan Mie Kuning dengan Metode Uji Kertas Tumerik - Yunicho, Yunicho; Sunu, Baharuddin; Rahman, Sartika Fatir; Anjani, Phitra (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2023)
Food is a source of energy for the body to be able to carry out various activities (Ministry of Health, 2015). We can find various types of food easily, both traditional food and food that follows society's taste trends. One of the foods that is a favorite food for all groups, both children, adults and the elderly, is meatballs. The problem with food circulating in the community is that traders want the food they sell to be durable or long-lasting, so many traders use chemical preservatives to make the food can be stored for a long time. The aim of this research is to determine whether or not there is borax in meatballs and yellow noodles sold at Central Market, Wajo District, Makassar City using the tumeric (turmeric) method. This research is a descriptive observational study with a cross sectional study design to identify the borax content in meatballs and yellow noodles. The results of this research show that the majority of samples examined in this study did not contain the chemical borax, namely 83.3% and only 16.7% of samples were found to contain borax. The meatballs sold at the Wajo District Central Market are suitable for consumption by the public, but still pay attention to the possibility of food that still uses the preservative borax.